Pengaruh Penggunaan Media Audiovisual Terhadap Hasil Belajar Siswa Pada Pembelajaran Seni Budaya (Musik) Di Kelas Xi SMA N 1 2x11 Enam Lingkung - Delvi Afriowanda Putri; Yos Sudarman (SENDRATASIK UNP, 2020)
This study aims to determine whether audiovisual media influences students’ learning outcomes in Cultural Arts (music) at class XI of SMA Negeri 1 2X11 Enam Lingkung. This type of research was an experimental study with a population of students of SMA Negeri 1 2X11 Enam Lingkung Padang Pariaman Regency. The variables in this study are the independentand the dependent variable. This research instrument used were the objective questions for the initial test (pretest) and objective questions for the final test (post-test). The techniques in analyzing data were normality test, homogeneity test, and hypothesis test. The results of the study show that there are differences of musical art learning outcomes between the use of audiovisual media withconventional methodin the learning of Cultural art (Music) in the even semester in SMAN 1 2X11 Enam Lingkung. This is proven through hypothesis testing with tarithmetic= 3.628 and ttable= 2.008. It can be concluded that, trithmetic>ttable in  = 5% thenH0 is rejected and H1is accepted.